2007
DOI: 10.2298/aci0701125s
|View full text |Cite
|
Sign up to set email alerts
|

Dieulafoy’s lesion: Rare cause of massive upper gastrointestinal bleeding

Abstract: Dieulafoy's lesion is an unusual and potentially life-threatening cause of massive, recurrent gastrointestinal bleeding. Its reported incidence as a source of upper gastrointestinal bleeding ranges from 0.3-6.7%. Dieulafoy's lesion is most commonly located in the proximal stomach (75% of cases). Lesion typically occur within 6 to 10 cm of the esophagogastric junction, generally along the lesser curvature of the stomach. Similar lesions have been identified in the esophagus, duodenal bulb, jejunum, ileum, color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The active bleeding during procedure was an important key to elucidate the lesion's nature. As a matter of fact, to diagnose a Dieulafoy's Lesion may be challenging even to an experienced endoscopist (Stojakov et al, 2007;Nojkov & Cappell, 2015). Previous studies demonstrated that even 49% of DL were identified on initial endoscopy and 33% of the patients required a repeted endoscopy (Reilly & Al-Kawas, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The active bleeding during procedure was an important key to elucidate the lesion's nature. As a matter of fact, to diagnose a Dieulafoy's Lesion may be challenging even to an experienced endoscopist (Stojakov et al, 2007;Nojkov & Cappell, 2015). Previous studies demonstrated that even 49% of DL were identified on initial endoscopy and 33% of the patients required a repeted endoscopy (Reilly & Al-Kawas, 1991).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 This lesion, which is frequently observed on the lesser curve of the stomach, is responsible for 0.3-6.7% of upper gastrointestinal hemorrhages. 3 It is more frequent in middle and older ages and more common in men. Endoscopic methods took place of surgery for treatment because of a high success rate.…”
Section: Introductionmentioning
confidence: 99%
“…This medical condition usually presents with a large tortuous arteriole in the stomach wall that erodes and bleeds. In addition, this lesion is generally located at the lesser curvature of the stomach within 6 to 10 cm of the esophagogastric junction (Stojakov et al, 2007). It consists of a single large tortuous arteriole that does not exert normal branching or has a branch 1-5 mm in diameter (Fig 2 & 3).…”
Section: Introductionmentioning
confidence: 99%